Malnutrition and risk of procedural complication in patients with atrial fibrillation undergoing catheter ablation. (24th May 2021) - Kim, D; Yu, HT; Kim, TH; Uhm, JS; Joung, B; Lee, MH; Pak, HN
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health and Welfare of Korea Ministry of Science, ICT & Future Planning of Korea Background: Malnutrition is common in the elderly, even in developed countries, and increases mortality. Purpose:  To investigate the prevalence and prognostic value of malnutrition among patients with atrial fibrillation (AF) which is a type of metabolic disease. Methods: We included 3, 239 patients (age 58.5 ± 10.8 years, 73.2% male, 67.7% paroxysmal type) undergoing de novo AF catheter ablation (AFCA) between 2009 and 2020. Nutritional status was assessed using controlling nutritional status (CONUT) score. The associations between malnutrition and the risk of AFCA complications or long-term rhythm outcome were evaluated by multivariable logistic regression. Results: Among 3, 239 patients, 1, 005 (31.0%) patients had malnutrition; 991 (30.6%) with mild (CONUT scores 2-4) and 14 (0.4%) with moderate-to-severe (CONUT scores ≥5) malnutrition. Overall complication rates after AFCA were 3.3% in normal nutrition, 4.2% in mild malnutrition, and 21.4% in moderate to severe malnutrition, respectively (P for trend = 0.031). Major complication rates were 1.9%, 2.6%, and 14.3% in normal nutrition, mild malnutrition, and moderate to severe malnutrition (P for trend = 0.042). After multivariable adjustment, moderate-to-severe malnutrition status was associated with increased risks of overall (OR 8.215 [2.199-30.691], P = 0.002) and major (OR 7.392 [1.568-34.837], P = 0.011) complications compared with normal nutrition. However, CONUT score did not affect the long-term rhythm outcome during the mean follow-up of 40 (interquartile range 18-74) months (log-rank P = 0.760). Conclusion: Malnutrition is common in patients undergoing AFCA. Those with moderate-to-severe malnutrition status were at substantially higher risk of complications after AFCA.